Elevated Adipsin and Reduced C5a Levels in the Maternal Serum and Follicular Fluid During Implantation Are Associated With Successful Pregnancy in Obese Women - Ramanjaneya, Manjunath; Diboun, Ilhame; Rizwana, Najeha; Dajani, Yaser; Ahmed, Lina; Butler, Alexandra E.; Almarzooqi, Thoraya Ali; Shahata, Mohammed; Al Bader, Moza Khalaf; Elgassim, Einas; Burjaq, Hasan; Atkin, Stephen L.; et al. (Frontiers in Endocrinology, 2022)
Introduction: Complement factors mediate the recruitment and activation of immune cells are associated with metabolic changes during pregnancy. The aim of this study was to determine whether complement factors in the maternal serum and follicular fluid (FF) are associated with in vitro fertilization (IVF) outcomes in overweight/obese women. Methods: Forty overweight/obese (BMI=30.8±5.2 Kg/m2) females, 33.6±6.3 years old, undergoing IVF treatment for unexplained infertility were recruited. Baseline demographic information including biochemical hormonal, metabolic, inflammatory markers and pregnancy outcome were collected. Levels of 14 complement markers (C2, C4b, C5, C5a, C9, adipsin, mannose-binding lectin, C1q, C3, C3b/iC3b, C4, Factor B, Factor H and properdin) were assessed in the serum and FF and compared to IVF outcome, inflammatory and metabolic markers using multivariate and univariate models. Results: Out of 40 IVF cycles, 14 (35%) resulted in pregnancy. Compared to women with failed pregnancies, women with successful pregnancies had higher levels of adipsin in the serum and FF (p=0.01) but lower C5a levels (p=0.05). Serum adipsin levels were positively correlated with circulating levels of vitamin D (R=0.5, p=0.02), glucagon (R=0.4, p=0.03), leptin (R=0.4, p=0.01), resistin (R=0.4, p=0.02), visfatin (R=0.4, p=0.02), but negatively correlated with total protein (R=-0.5, p=0.03). Higher numbers of top-quality embryos were associated with increased levels of C3, properdin, C1q, factors H and B, C4 and adipsin, but with reduced C2 and C5a levels (p≤0.01). Conclusions: Higher adipsin and lower C5a levels in the maternal serum during implantation are potential markers of successful outcome in obese women undergoing IVF-assisted pregnancies.